2018
DOI: 10.1021/acs.jpcc.8b05148
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid Mixture Expands the Potential Window and Capacitance of a Supercapacitor in Tandem

Abstract: Mixing room temperature ionic liquids (RTIL) may optimize electrolyte properties for the better performance of electrical double layer capacitors (EDLCs). To understand the composition effects, we theoretically investigate the potential window, interfacial structure, capacitance, and energy density of RTIL mixtures consisting of one common cation and two anions of different sizes. A combination of quantum density functional theory (QDFT) and classical density functional theory (CDFT) calculations indicates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 72 publications
1
22
0
Order By: Relevance
“…As stated above, it is possible to relate the HOMO-LUMO gaps of the IL ion-pairs to their liquid phase electrochemical windows [11]. From our calculated HOMO-LUMO gaps, it would seem that EMIM is the most electrochemically stable cation, followed by DEME and PYR1,4.…”
Section: The Description Of the [Deme]mentioning
confidence: 69%
See 2 more Smart Citations
“…As stated above, it is possible to relate the HOMO-LUMO gaps of the IL ion-pairs to their liquid phase electrochemical windows [11]. From our calculated HOMO-LUMO gaps, it would seem that EMIM is the most electrochemically stable cation, followed by DEME and PYR1,4.…”
Section: The Description Of the [Deme]mentioning
confidence: 69%
“…Ilawe et al also found that the ωB97X-D functional is superior to M06-2X and B3LYP [10]. Lian et al also used the ωB97X-D functional and claimed that it is quantitatively accurate for predicting the electronic properties of individual ions in vacuum [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As established in previous works, the cathodic limits of each anion or cation can be reasonably estimated from the LUMO and the anodic limits are related to the HOMO energies of the anion or the cation. For each ionic species, the cathodic and anodic limit potentials, V CL and V AL , are expressed as VCL=εLUMOe VAL=εHOMOe where ε LUMO and ε HOMO are the LUMO and HOMO energy levels, and e is the unit charge.…”
Section: Theoretical Methodsmentioning
confidence: 95%
“…For the first time, we demonstrated the CVD of an IL. The strength of the IL-CVD method to deposit ionogel microstructures and the ability of the vaporized precursors to conformally coat three-dimensional substrates will facilitate leveraging the properties of ILs in a range of devices and applications including microsupercapacitors and microbatteries, [80][81][82][83] solar cells, [11,12] actuators, [19] sensors, [15,16,29,30] membrane separation processes, [84] and display textiles. [85]…”
Section: Angewandte Chemiementioning
confidence: 99%